The beauty of holiness : Anglicanism & architecture in colonial South Carolina - Nelson, Louis P. (Richard Hampton Jenrette series in architecture & the decorative arts., 2008)
In The Beauty of Holiness, he tells the story of the Churchof England in colonial South Carolina, revealing how the colony'sAnglicans negotiated the tensions between the persistence ofseventeenth-century religious practice and the rising tide ofEnlightenment thought and sentimentality.